The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jbm.b.34989
|View full text |Cite
|
Sign up to set email alerts
|

3D‐bulk to nanoforms of modified hydroxyapatite: Characterization and osteogenic potency in an in vitro 3D bone model system

Abstract: Synthetic bioceramics are replacing conventional methods of treating bone defects with autografts owing to the high demand of bone substitutes, with their Surface topography and size contributing to favor cytocompatibility in tissue regeneration. This experimental study deals with the comparative evaluation of the physical characterizations of four different in‐house synthesized bioceramics from 3D‐bulk to nanoforms of hydroxyapatite (HA), Biphasic calcium phosphate (BCP), Strontium doped hydroxyapatite (SrHA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The viability results showed no cytotoxic effect of the scaffolds on the hUC-MSCs over a period of 3 days, and a time-dependent proliferation pattern was observed ( Figure 2 b). Many studies using biological activity assays have shown that BCP scaffolds doped with metals are not toxic to MC3T3-E1 cells [ 25 , 47 ], human umbilical vein endothelial cells [ 48 ], bone mesenchymal stem cells [ 49 ], rabbit-adipose-derived mesenchymal stem cells [ 50 ], human osteoblast-like MG-63 cells [ 51 ] and human mesenchymal stem cells [ 13 ]. Among the tested compositions, the BCP-6Sr2Mg2Zn scaffolds proved to be the most promising.…”
Section: Discussionmentioning
confidence: 99%
“…The viability results showed no cytotoxic effect of the scaffolds on the hUC-MSCs over a period of 3 days, and a time-dependent proliferation pattern was observed ( Figure 2 b). Many studies using biological activity assays have shown that BCP scaffolds doped with metals are not toxic to MC3T3-E1 cells [ 25 , 47 ], human umbilical vein endothelial cells [ 48 ], bone mesenchymal stem cells [ 49 ], rabbit-adipose-derived mesenchymal stem cells [ 50 ], human osteoblast-like MG-63 cells [ 51 ] and human mesenchymal stem cells [ 13 ]. Among the tested compositions, the BCP-6Sr2Mg2Zn scaffolds proved to be the most promising.…”
Section: Discussionmentioning
confidence: 99%